From Lyrics to Lexis: Exploring Students’ Perceptions of Modified English Songs in Vocabulary Learning - La Sunra; Syarifah Farahdiba; Melinda (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This descriptive qualitative study explores seventh-grade students’ perceptions of using modified English songs to enhance vocabulary learning at SMPN 3 Minasatene, Indonesia. The research was conducted over four weeks, during which data were collected through semi-structured interviews with three students selected via purposive sampling. The interviews were analyzed thematically following the procedures of data reduction, display, and conclusion drawing. The findings reveal that students viewed modified songs as engaging and helpful tools for learning vocabulary. Adapting song lyrics to match students’ proficiency levels helped them understand word meanings more easily, improve pronunciation, and apply new vocabulary in appropriate contexts. Moreover, the use of songs created a more enjoyable and motivating classroom environment, enhancing students’ confidence in learning English. These results suggest that integrating modified songs into vocabulary instruction can strengthen both linguistic and affective aspects of learning by providing meaningful, memorable, and student-centered language experiences. The study highlights the importance of creative instructional media for young learners and encourages teachers to incorporate modified songs as a practical approach to vocabulary development in English language classrooms.